2019
DOI: 10.1182/bloodadvances.2018028753
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils acquire antigen-presenting cell features after phagocytosis of IgG-opsonized erythrocytes

Abstract: Neutrophils are particularly well known for their antimicrobial function. Although historically they are regarded as strictly a phagocyte of the innate immune system, over time it has become clear that neutrophils are versatile cells with numerous functions including innate and adaptive immune regulation. We have previously described a role for human neutrophils in antibody-mediated red blood cell (RBC) clearance. Under homeostatic conditions, neutrophils do not take up RBCs. Yet, when RBCs are immunoglobulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
2
40
0
3
Order By: Relevance
“…Neutrophils can also initiate adaptive immune responses by directly presenting antigens themselves, or by acting as accessory cells, to support T-cell responses. For instance, human neutrophils upregulate MHC-II and co-stimulatory molecule (CD40 and CD80) expression and can present antigens to CD4 + T-cells following phagocytosis [58]. Neutrophil acquisition of these antigen-presenting properties (MHC-II, CD40, and CD80 expression) is associated with increased activation and proliferation of CD4 + T-cells in response to tetanus toxoid.…”
Section: Neutrophils Influence Innate and Adaptive Immunitymentioning
confidence: 99%
“…Neutrophils can also initiate adaptive immune responses by directly presenting antigens themselves, or by acting as accessory cells, to support T-cell responses. For instance, human neutrophils upregulate MHC-II and co-stimulatory molecule (CD40 and CD80) expression and can present antigens to CD4 + T-cells following phagocytosis [58]. Neutrophil acquisition of these antigen-presenting properties (MHC-II, CD40, and CD80 expression) is associated with increased activation and proliferation of CD4 + T-cells in response to tetanus toxoid.…”
Section: Neutrophils Influence Innate and Adaptive Immunitymentioning
confidence: 99%
“…However, years of research have shown neutrophils in a different light such as they have a range of cytokines and effector molecules. They are also involved in numerous effector functions and can regulate the innate and adaptive immune system (27). Neutrophils are also known to have an important role as a modulator of inflammation and cancer immunology.…”
Section: Brief Overview Of Cell Subtypes Of Phagocytosismentioning
confidence: 99%
“…Finally, it is also worth mentioning the upregulation of MHC-II molecules observed in CD11b + Ly6G hi and CD11b + Ly6G int neutrophils sorted from infected/treated mice. This observation broadens the immunomodulatory role of neutrophils upon mAb-treatment as it suggests that neutrophils might acquire antigen-presenting cell features and induce antigen-specific T-cells responses (Lok et al, 2019; Meinderts et al, 2019; Vono et al, 2017). In agreement with this, it has been shown that upon ex vivo stimulation with IgG immune complex (IC) or viral cognate antigens, neutrophils upregulated expression of MHCII and costimulatory molecules and increased T cell activation.…”
Section: Discussionmentioning
confidence: 78%